Cross-Sectoral Coordination in Peatland Management Policy - Zulkarnaini; Mimin Sundari Nasution; Gevisioner (CV. AFDIFAL MAJU BERKAH, 2021)
This paper analyzes the many problems caused by errors in peatland management in Riau Province. In the province which is the largest peat area on the island of Sumatra, there is a decline in the quality of peat swamp land caused by various interests, especially the exploitation of natural resources that considers the level of sustainability and sustainability. This study uses a policy analysis approach. The results of the study show that there is a lack of attention to the importance of peatlands in supporting sustainable development and that there is no institution that is given the responsibility for managing and protecting the existence of peatlands. Peatlands are heavily affected by various conflicts and overlapping policies. As a result, various forms of peatland management activities in Riau Province are still carried out by certain agencies with an inadequate level of understanding of conservation issues. In the case of clearing agricultural land or settlements on deep peatlands that do not pay attention to water and land conservation aspects, even though such areas must be protected